Phylogenetic classification and palm-inflorescence anthophily of the Colocasiomyia zeylanica species group (Diptera: Drosophilidae), with descriptions of five new species - Zhang, Guang; Gao, Jian-Jun; Takano, Kohei Takenaka; Yafuso, Masako; Suwito, Awit; Meleng, Paulus Ak; Toda, Masanori J. (Zootaxa, 2023)
The zeylanica group is one of the six species groups of the anthophilic genus Colocasiomyia de Meijere in the family Drosophilidae. In addition to two known species, five morphospecies have been recognized as members of this species group but left undescribed formally. In this study, species delimitation of these putatively new species was determined by barcoding of the mitochondrial COI (cytochrome c oxydase subunit I) gene and morphological comparison. Phylogenetic relationships within the genus Colocasiomyia were inferred by a cladistic analysis of 89 morphological characters. Based on the results of these analyses, we redefined the zeylanica species group and established two subgroups within it: the zeylanica subgroup comprised of C. zeylanica, C. nepalensis, C. pinangae sp. nov., C. besaris sp. nov. and C. luciphila sp. nov., and the oligochaeta subgroup of C. oligochaeta sp. nov. and C. grimaldii sp. nov. In addition, we briefly address the anthophilic habits of drosophilid flies using palm (Arecaceae) inflorescences, especially of the zeylanica group, compiling scattered collection records from the Oriental and Papuan regions.